Examining the Challenges and Opportunities of ChatGPT in EFL Education: A Systematic Literature Review - Slamet, Joko; Basthomi, Yazid (Journal of University Teaching and Learning Practice, 2025)
English as a Foreign Language (EFL) education faces challenges in effectively promoting language learning, and the integration of ChatGPT holds promise as a solution. This systematic literature review (SLR) aims to comprehensively explore the challenges and opportunities of ChatGPT integration in the EFL context, specifically focusing on its impact on learner autonomy and self-directed learning. Through a systematic search across ScienceDirect, Education Resources Information Center (ERIC), and Google Scholar. with Full text databases, 13 relevant articles were identified and analyzed. The review revealed several challenges associated with ChatGPT integration, including language accuracy issues, limited context sensitivity, and the need to strike a balance between technology and human interaction. However, it also identified promising opportunities, such as personalized and interactive language learning experiences, immediate feedback provision, and enhanced learner engagement. These findings underscore the importance of considering both challenges and opportunities in ChatGPT integration. To optimize the benefits while maintaining the essential role of human interaction, adequate training for educators is crucial. This SLR significantly contributes to understanding the challenges and opportunities related to ChatGPT integration in EFL education. The identified lacunae and recommendations provide valuable insights for EFL educators, researchers, and policymakers, guiding effective implementation strategies to improve language learning experiences. Further research is needed to explore the pedagogical implications and long-term effects of ChatGPT integration in diverse EFL contexts. Addressing these voids will enable EFL education to harness the full potential of ChatGPT, enhancing language learning outcomes, fostering learner autonomy and self-directed learning, and transforming instructional practices.